2020
DOI: 10.1029/2020gl088533
|View full text |Cite
|
Sign up to set email alerts
|

Puzzling Haze Events in China During the Coronavirus (COVID‐19) Shutdown

Abstract: It is a puzzle as to why more severe haze formed during the New Year Holiday in 2020 (NYH-20), when China was in an unprecedented state of shutdown to contain the coronavirus (COVID-19) outbreak, than in 2019 (NYH-19). We performed a comprehensive measurement and modeling analysis of the aerosol chemistry and physics at multiple sites in China (mainly in Shanghai) before, during, and after NYH-19 and NYH-20. Much higher secondary aerosol fraction in PM 2.5 were observed during NYH-20 (73%) than during NYH-19 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
153
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 186 publications
(169 citation statements)
references
References 50 publications
16
153
0
Order By: Relevance
“…The results of this study and others commonly showed that the extreme lockdown inevitably harmed the economy, but was not efficiently helpful in improving air quality ( Chang et al, 2020 ; Cheval et al, 2020 ; Huang et al, 2020 ; Le Quéré et al, 2020 ; Le et al, 2020 ; Siciliano et al, 2020 ). In multiple studies, the enhanced secondary pollution of aerosols was caused by the increase in oxidative capacity due to the increase in ozone ( Chang et al, 2020 ; Huang et al, 2020 ). In the Beijing-Hebei-Tianjin region, the increase of heterogeneous aerosol chemistry promoted aerosol pollution under high relative humidity conditions ( Le et al, 2020 ).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The results of this study and others commonly showed that the extreme lockdown inevitably harmed the economy, but was not efficiently helpful in improving air quality ( Chang et al, 2020 ; Cheval et al, 2020 ; Huang et al, 2020 ; Le Quéré et al, 2020 ; Le et al, 2020 ; Siciliano et al, 2020 ). In multiple studies, the enhanced secondary pollution of aerosols was caused by the increase in oxidative capacity due to the increase in ozone ( Chang et al, 2020 ; Huang et al, 2020 ). In the Beijing-Hebei-Tianjin region, the increase of heterogeneous aerosol chemistry promoted aerosol pollution under high relative humidity conditions ( Le et al, 2020 ).…”
Section: Discussionmentioning
confidence: 56%
“…and South and North America ( Bauwens et al, 2020 ; Ma and Kang, 2020 ; Siciliano et al, 2020 ). However, with the remarkable reduction of emissions during the COIVD-19 outbreak, unexpected air pollution rose in multiple areas in China, such as the Beijing-Tianjin-Hebei and Yangtze River Delta regions ( Chang et al, 2020 ; Le et al, 2020 ; Wang et al, 2020 ). Le et al (2020) proposed that the air pollution was caused by the anomalously high humidity promoting heterogeneous aerosol chemistry, along with stagnant airflow and continuous emissions from power plants and petrochemical facilities, contributing to severe haze formation.…”
Section: Introductionmentioning
confidence: 99%
“…The dates correspond to the trajectory maps ( Figure S1) which suggest particulate sources to be local. A recent study in Shanghai during the Chinese New Year holiday in late February 2020 [24] also reports severe haze despite reduced NO 2 levels, where measurements of atmospheric chemistry and physics demonstrated that the increase in fine particulates was due to secondary aerosol formation, predominantly nitrate aerosols.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of factors is likely responsible, the foremost of which may be enhanced production of secondary particulates. These are formed when reductions in NOx result in increased ozone formation, thus increasing the oxidizing capacity of the atmosphere [24] allowing the production of secondary particulates such as nitrates, sulphates, and organic compounds. This production involves condensation around existing particles or new particles, and the resulting particulate compounds comprise mainly sulphates, nitrates, and organic compounds [25] which are less absorbing in nature [26].…”
Section: Discussionmentioning
confidence: 99%
“…To control the spread of the 2019 novel coronavirus (COVID-19), China launched a level-I response to this public health emergency in 30 provinces, autonomous regions, and municipalities as early as January 25, and was the first country to shut down commercial activities, restrict travel, and require its people to stay home ( Tian et al, 2020 ; Wang et al, 2020a , Wang et al, 2020b ). From January 24, 2020, Hubei was the first province in China to implement these restrictions, which are believed to have caused large reductions in air pollutant emissions over large regions in China ( Huang et al, 2020 ; Chang et al, 2020 ; Shi and Brasseur, 2020 ). Such anomalies in air pollutants (PM 2.5 , NO 2 , and O 3 ) diminished near the end of February 2020, when restrictions related to COVID-19 began to be eased and people outside of Hubei province started to return to work ( Huang et al, 2020 ; Wang et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%